Liraglutide hospital discharge trial: A randomized controlled trial comparing the safety and efficacy of liraglutide versus insulin glargine for the management of patients with type 2 diabetes after hospital discharge. Issue 6 (31st March 2021) - Pasquel, Francisco J.; Urrutia, Maria A.; Cardona, Saumeth; Coronado, Karla W. Z.; Albury, Bonnie; Perez‐Guzman, Mireya C.; Galindo, Rodolfo J.; Chaudhuri, Ajay; Iacobellis, Gianluca; Palacios, Juan; Farias, Javier M.; Gomez, Patricia; et al.
Abstract: Aim: To compare a glucagon‐like peptide‐1 receptor agonist with basal insulin at hospital discharge in patients with uncontrolled type 2 diabetes in a randomized clinical trial. Methods: A total of 273 patients with glycated haemoglobin (HbA1c) 7%–10% (53–86 mol/mol) were randomized to liraglutide (n = 136) or insulin glargine (n = 137) at hospital discharge. The primary endpoint was difference in HbA1c at 12 and 26 weeks. Secondary endpoints included hypoglycaemia, changes in body weight, and achievement of HbA1c <7% (53 mmol/mol) without hypoglycaemia or weight gain. Results: The between‐group difference in HbA1c at 12 weeks and 26 weeks was −0.28% (95% CI −0.64, 0.09), and at 26 weeks it was −0.55%, (95% CI −1.01, −0.09) in favour of liraglutide. Liraglutide treatment resulted in a lower frequency of hypoglycaemia <3.9 mmol/L (13% vs 23%; P = 0.04), but there was no difference in the rate of clinically significant hypoglycaemia <3.0 mmol/L. Compared to insulin glargine, liraglutide treatment was associated with greater weight loss at 26 weeks (−4.7 ± 7.7 kg vs −0.6 ± 11.5 kg; P < 0.001), and the proportion of patients with HbA1c <7% (53 mmol/mol) without hypoglycaemia was 48% versus 33% ( P = 0.05) at 12 weeks and 45% versus 33% ( P = 0.14) at 26 weeks in liraglutide versus insulin glargine. The proportion of patients with HbA1c <7% (53 mmol/mol) without hypoglycaemia and no weight gain was higher with liraglutide at 12 (41% vs 24%, P = 0.005) and 26 weeks (39% vs 22%; P = 0.014). The incidence of gastrointestinal adverse events was higher with liraglutide than with insulin glargine ( P < 0.001). Conclusion: Compared to insulin glargine, treatment with liraglutide at hospital discharge resulted in better glycaemic control and greater weight loss, but increased gastrointestinal adverse events.